Ensure the Right of Citizens to Work: Problems of Domestic and International Regulation - Berdiyarova, Zh.; Serikbekova, S.; Babajanyan, Y. (International Journal of Environmental and Science Education, Vol. 11, No. 11, 4801-4811, 2016)
The purpose of this research is to examine the legal problems of ensuring the right to work of citizens in the Republic of Kazakhstan and to find the conformity of labor laws in the Republic of Kazakhstan to international standards. Using the method of comparison analysis of the legislation of the Republic of Kazakhstan and norms of international treaties and agreements, the authors determine that in order to improve the labor legislation of the Republic of Kazakhstan and to prevent labor and social conflicts, it is necessary to 1) amend and supplement the Constitution of the Republic of Kazakhstan dated August 30, 1995, with a view to ensuring the right to work of citizens of the Republic of Kazakhstan; 2) similarly amend the Labor Code of the Republic of Kazakhstan and the Law “On Employment” of the Republic of Kazakhstan. Thus, the submissions may be practically important for the improvement of the labor legislation of the Republic of Kazakhstan, prevention of labor and other social conflicts.
Keywords: the Republic of Kazakhstan, citizens’ right to work, freedom of labor, regulation of unemployment, discrimination against workers